Complex diffractometrical investigation of structural and compositional irregularities in GaAs:Si/GaAs films heavily doped with silicon - Datsenko, L.I.; Klad’ko, V.P.; Lytvyn, P.M.; Domagala, J.; Machulin, V.F.; Prokopenko, I.V.; Molodkin, V.B.; Maksimenko, Z.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Complex of X-ray diffractometrical investigations, both angular and spectral dependences of a reflectivity for quasi-forbidden reflections, enable not only to discover structural microdefects and to measure their radii r as well as concentration n, but also to determine the level of nonstoichiometry, , where are concentrations of lattice components A and B, respectively. In the case of angular dependencies, the two-dimensional maps of diffuse scattering in a reciprocal space for a characteristic radiation were plotted for GaAs:Si/GaAs films heavily doped by Si (up to 10²⁰ cm⁻³) using a three-crystal spectrometer (TCS). In the case of spectral (energy) dependencies, reflectivity were measured using a single crystal spectrometer (SCS) and white beam radiation. In both cases the formulae of the Molodkin dynamical scattering theory developed for real crystals with homogeneously distributed microdefects were used by the fitting procedure of the calculated intensities to those measured using TCS or SCS for (200) and (400) reflections of X-rays. The TCS maps were registred for Cu Ka - radiation by the Phillips three-crystal diffractometer. Good agreement between the two groups of the and parameters of microdefects (precipita¬tes) was shown for some GaAs film (r₁ = 3.5 mm, n₁ = 4.3*10⁶ cm⁻³; r₂ = 4.8 μm, n₂ = 9.4*10⁶ cm⁻³) . Parameter D = 0.009 (Ga excess) was determined too.